Screening of Rice Genotypes for Resistance Against Bacterial Blight Disease - Jirankali, Jyoti P.; Deepak, C. A.; Chethana, B. S.; Sandesh, G. M.; Nikhil, G.; Rajanna, M. P. (International Journal of Economic Plants, 2023)
A study was undertaken at V. C. Farm, Mandya, Karnataka, India during 2020 to screen the genotypes against BLB under natural field conditions. Host Plant resistance is an important component of an integrated management program for this disease. Among the 102 rice genotypes screened under natural epiphytotic condition at Zonal Agricultural Station, V. C. Farm, Mandya, none of them were found immune against bacterial leaf blight. So, in the study, plants were assessed by measuring disease severity (% of leaf diseased) and area under the disease progress curve (AUDPC). The pathogenicity of Xoo was tested on IRRI rice cultivars, inoculation was conducted at the maximum tillering stage, and the lesion length was measured after 14 days of inoculation. An attempt was made to phenotypically characterize a set of 102 Genotypes from IRRI for BLB resistance by artificially inoculaton using clipping method. Out of the 102 genotypes and two checks tested, it was observed that five entries viz., IRGC 125853, IRGC 126264, IRGC 132357, IRGC 122088 IRGC 125658 and Improved Samba Mahsuri were highly resistant with score of 1. Only one entry (IRGC 125754) was resistant with score of 3, 33 lines being moderately resistant with score of 5 and 43 lines were susceptible with score of 7. 20 lines and also the susceptible check Jyothi-PTB 39, had the highest susceptibility with a phenotypic score of 9.